2018
DOI: 10.3389/fphys.2018.00765
|View full text |Cite
|
Sign up to set email alerts
|

Src Plays an Important Role in AGE-Induced Endothelial Cell Proliferation, Migration, and Tubulogenesis

Abstract: Advanced glycation end products (AGEs), produced by the non-enzymatic glycation of proteins and lipids under hyperglycemia or oxidative stress conditions, has been implicated to be pivotal in the development of diabetic vascular complications, including diabetic retinopathy. We previously demonstrated that Src kinase played a causative role in AGE-induced hyper-permeability and barrier dysfunction in human umbilical vein endothelial cells (HUVECs). While the increase of vascular permeability is the early event… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 38 publications
2
25
0
Order By: Relevance
“…Our data are in line with previous studies showing that dicarbonyls induce endothelial dysfunction via oxidative stress, inflammatory responses, senescence or apoptosis (Jang et al, 2017;Liu et al, 2012;Navarrete Santos et al, 2017;Sliman et al, 2010;Wang et al, 2019;Yamawaki and Hara, 2008) and that AGEs interfere via RAGE-dependent signaling processes in endothelial cells (Chen et al, 2020;Li et al, 2018;Ravi et al, 2020). Until now, however, the impact of dicarbonylinduced changes of protein abundance and intracellular protein modifications on endothelial function has not been thoroughly investigated.…”
Section: Discussionsupporting
confidence: 92%
“…Our data are in line with previous studies showing that dicarbonyls induce endothelial dysfunction via oxidative stress, inflammatory responses, senescence or apoptosis (Jang et al, 2017;Liu et al, 2012;Navarrete Santos et al, 2017;Sliman et al, 2010;Wang et al, 2019;Yamawaki and Hara, 2008) and that AGEs interfere via RAGE-dependent signaling processes in endothelial cells (Chen et al, 2020;Li et al, 2018;Ravi et al, 2020). Until now, however, the impact of dicarbonylinduced changes of protein abundance and intracellular protein modifications on endothelial function has not been thoroughly investigated.…”
Section: Discussionsupporting
confidence: 92%
“…Similar phenomena were observed where treatment of cells with Src blockers abolished Src phosphorylation (Figure 6(d)) and VE-Cadherin phosphorylation (Figure 6(e)) induced by IS implying that PP2 has a potential to inhibit the increased activity of Src mediating VE-Cadherin and reduce hyperpermeability induced by IS. These results are also in agreement with studies which reported that phosphorylation of Src gives rise to endothelial hyperpermeability due to stimulation by Advanced Glycation End-products (AGEs) and PP2 downregulated Src expression illustrating that inactivation of Src decreased AGE-induced HUVEC proliferation, migration, and tube formation [62]. Next, we observed the effect of RES on cytosolic AHR and then evaluated coincubation with IS (Figure 7).…”
Section: Discussionsupporting
confidence: 91%
“…The MAPKs signaling cascades activated by RAGE can be regulated by the adaptor molecule mDia-1 (diaphanous related formin 1), a member of the GEF (guanine nucleotide exchange factor) family to activate the Rac1/Cdc42 pathway. Moreover, the RAGE cytosolic domain is connected to the tyrosine kinase protein, Src, which is also related to several downstream signal factors, such as ERK1/2, p38 MAPK, JNK (Basta, 2008;Lee et al, 2015;Zhang et al, 2015;Li et al, 2018;Riuzzi et al, 2018). To further explore the signal pathway of the heat-induced hyper-permeability in which RAGE is involved, a series of experiments were conducted, such as transfecting with siRNA, adenovirus, or pre-incubating with blocking antibody.…”
Section: Discussionmentioning
confidence: 99%